BANK INFAQ: RISK MANAGEMENT IN THE PROVISION OF UMKM CAPITAL DURING COVID-19 - Purnomo, Agus; Maulida, Atika Zahra (Al-Infaq: Jurnal Ekonomi Islam, 2023)
Bank Infaq is an Islamic public financial instrument that has economic empowerment activities. Infaq fund collection is carried out by infaq banks offline and online. This research was conducted to reduce risk and provide solutions to reduce the risk of jamming in the provision of business capital during the covid 19 pandemic. The study used qualitative methods by conducting interviews with the management, collection, and distribution of infaq funds. In collecting research data using the purposive sampling technique, the researcher takes data according to the categories that have been determined by the researcher at random. The analysis of the research results explains the collection, distribution, and risk management in providing UMKM business capital. Infaq funds collected by infaq banks have increased every year. Infaq funds will be channeled in economic empowerment activities such as providing business capital to UMKM actors affected by COVID 19. The distributed business capital will be monitored and evaluated to reduce the risk of default (bad credit).